Penelitian pengaruh DPT sebagai blowing agent terhadap ketahanan kikis dan kekerasan sol karet - Sesantiningsih, Titien Sayekti (Center for Leather, Rubber, and Plastic Ministry of Industry, Indonesia, 1989)
DPT is a blowing agent which is used for the production of soft, medium and hard types of microselluler sole. This type of blowing agent if the rubber compound, will influence the hardness and abrasive resistant of the sole.Using of 3,5 part blowing agent will give the best quality of rubber compound with the hardness 68,33 shore A and th abrasive resistant 2,60 mm3 / kgrm.